Promise of sustainable CO2 utilisation technology to boost European Industry. (Research'eu results magazine)
Holding its final conference in Brussels in June 2016, the EU-funded SCOT project has showcased its innovative work over the past 3 years on building Europe's capacity for the development of innovative CO2 utilisation and recycling technologies.